Analysis of MADS-box genes and heat stress in barley (Hordeum vulgare) - Callens, Cindy (2020)
Barley is a widely grown, economically important cereal crop used for stock feed, malting and brewing. Fundamental understanding of the underlying genetic network controlling floral organ development is essential for potential modification of floral architecture for plant breeding. ABCDE-model MADS-box proteins are a type of MADS-box family transcription factors that contain a conserved 60 amino acid MADS-box motif and that are involved in inflorescence and flower development. In the dicot model Arabidopsis thaliana and in crops like rice (Oryza sativa), maize (Zea mays) and wheat (Triticum aestivum) most of the ABCDE-model MADS-box flowering genes have been identified. In barley (Hordeum vulgare) however, only a select number of MADS-box flowering genes have been investigated. Identifying the role and structure of the ABCDE-model MADS-box genes in barley floral development could shed a light on the evolutionary differences between barley and closely related crops and the development of their inflorescences and flower morphogenesis. In this thesis I aimed to identify the expression patterns of the ABCDE-model MADS-box genes in barley by qRT-PCR and in situ hybridization. To investigate the function of the B-class genes in barley the CRES-T dominant repression system, also known as SRDX, was used. Results showed that the expression patterns of the ABCDE MADS-box genes are conserved in barley and that the B-class genes have a redundant function in stamens and lodicule development. MADS-box transcription factors have been shown to be involved in abiotic stress tolerance in several different species like tomato, rice and sheepgrass. Abiotic stresses, particularly global warming, are the major causes of crop yield losses by affecting fertility and seed set. Prior to analysis of the specific impact of abiotic stress on the MADS-box genes, it is important to understand the effects of abiotic stress on barley per se. Effects of heat stress on reproductive structures and fertility in barley have not been extensively investigated. In this thesis the effect of high temperature conditions on floral development in three commercial European spring barley varieties during two vulnerable reproductive stages, meiosis and mitosis, was examined by using fertility assays, 3-dimensional modelling, cytology and immunolabelling. Results showed that male reproductive organs are more vulnerable to heat stress than female reproductive organs and that certain varieties are more tolerant to heat stress.